PENGARUH LITERASI KEUANGAN TERHADAP MINAT INVESTASI MAHASISWA DI ERA DIGITAL - Raviel Aditya; Riska Faradilla Widiastuti; Arista Aulia Putri; Alishia Anggun Maharani; Nugraheni Nur Rossyda (Jurnal Ilmiah Manajemen dan Akuntansi, 2026)
Financial literacy is the ability of individuals to understand, access, evaluate, and utilize financial information and services to support effective, safe, and responsible financial decision-making. In the digital era, technological advancements and easy access to information have created broader opportunities for students to participate in various investment activities. This study aims to analyze the influence of financial literacy on students' investment interest in the digital era. The research employed a quantitative approach, with data collected through questionnaires distributed to university students. The results indicate that financial literacy has a positive and significant effect on students' investment interest. These findings suggest that higher levels of financial literacy are associated with greater investment interest among students. Therefore, improving financial literacy is an important factor in encouraging student participation in investment activities in the digital era.